القدرة التنافسية للصناعات الدوائية الأردنية(القياس والتحليل) - محمود, يوسف; صقر, محمد; النسور, عبدالحكيم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدفت هذه الدراسة إلى التعرف على واقع القدرة التنافسية في شركات الصناعة الدوائية الأردنية ومعرفة الوسائل والطرق المؤدية لزيادة إنتاجية ومبيعات تلك الشركات باعتبار أن الحصة السوقية في تلك الشركات هي إحدى مقاييس التنافسية التي تعتبر أهم مقومات نجاح تلك الشركات في ظل الانفتاح الاقتصادي، وتم لذلك الغرض دراسة العلاقة بين مؤشر التنافسية لقطاع الشركات وبعض المتغيرات الداعمة لمعنى التنافسية مثل متغيرات رأسمال الشركات والعمر الإنتاجي وعدد الأصناف الطبية المنتجة في الشركات وحجم المنفق على البحث العلمي وعدد العاملين في شركات الأدوية والعاملين في البحث العلمي والعاملين في التسويق ، وغيرها من المتغيرات. وبتطبيق ذلك على شركات صناعة الدواء الأردنية تبين أن هناك علاقة إيجابية بين مؤشر التنافسية (الحصة السوقية) وبين كُلّ من العدد الإجمالي للعاملين في الشركة ، العمر الإنتاجي للشركة ، وحجم الصادرات لتلك الشركات. This study aims at exploring the status of the competitive abilities of the Jordanian pharmaceutical industry and the means by which the production and sales of such companies can be raised; since their market share is taken into consideration in measuring the competitiveness of such companies, it is seen as one of the success factors in the light of economic openness. This paper also studies the relation between the competitiveness index of companies and other factors, such as capital, production age, the number of different medical productions, the expenditure on scientific research, the number of employees in pharmaceutical companies and in scientific research .and marketing. By applying this on Jordanian pharmaceutical industries shows that there is a positive relation between the competitiveness index (market share) and the total number of employees in the company, production age, and exports rate.